Reversible Three‐Dimensional Focusing of Visible Light with Ultrathin Plasmonic Flat Lens. Issue 7 (26th May 2013) - Chen, Xianzhong; Huang, Lingling; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Qiu, Cheng‐Wei; Zentgraf, Thomas; Zhang, Shuang
<x xml:space="preserve">Abstract</x> Metasurfaces with interfacial phase discontinuities provide a unique platform for manipulating light propagation both in free space and along a surface. Three‐dimensional focusing of visible light is experimentally exhibited as a bi‐functional phenomenon by controlling the radial orientation of identical plasmonic dipoles, generating a desired phase profile along the interface. With this technique, the in‐plane and out‐of‐plane refractions are manipulated by an ultrathin flat lens such that a beam can be focused into a 3D spot either in a real or virtual focal plane, which can be reversed via manipulation of the circularly polarized status of the incident light. Both the inverted real image and the upright virtual image of an arbitrary object are experimentally demonstrated using the same flat lens in the visible range, which paves the way towards robust application of phase discontinuity devices.